(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The article explains the theoretical justification of the possibility of using new types of additives obtained from local raw materials in the formation of quality indicators of bread and pasta products enriched with biologically active substances, minerals.